Study of hand washing practices in rural community of Pune, India - Pandve, Harshal T.; Chawla, P. S.; Giri, Purushottam A.; Fernandez, Kevin; Singru, Samir A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hand washing is well recognized preventive tool disease prevention. To study hand washing practices in rural community; Objectives: a]. To study medium of hand washing, b]. To determine any association between hand washing practices and some socio-demographic characteristics, c]. To study association between hand washing practices and certain infections. Methods:A community based observational study was conducted in five randomly selected villages in rural field practice area of medical college in Pune, Maharashtra. In house to house survey, interview was conducted on pre-tested questionnaire regarding hand washing practices. On site inspection of designated place for hand washing was also done. Statistical analysis: Percentages, Proportions and chi-square test. Results: A total of 1468 (799 males & 669 females) individuals participated in the study. Majority (37.23%) were from 21 to 40 years age-group. 698 were studied up to secondary grade. In 48.46% study participants the family was major source of information regarding importance of hand washing was family. 1167 (79.49%) were using soap and water, 117 (7.98%) used water and antiseptic solution for hand washing. 184 (12.53%) used only water for hand washing. 100% practiced hand washing after defecation. There was significant association between medium of hand washing and age-group, literacy status. Association was also found between the history of episode of upper respiratory tract infection and diarrhea with medium of hand washing. Conclusions:Majority of the study participants used water with soap for hand washing. This finding is encouraging and sustainable practice is recommended.